Learning how to work in the arts field in Portugal: a biographical approach to the migrant artists’ trajectories - Ferro, L.; Abrantes, P.; Veloso, L.; Lopes, J. T. (RUDN journal of Sociology, 2018)
The article considers the key dimensions of the life trajectories of the immigrant artists living in the Lisbon metropolitan area focusing on those related to the socialization process both in formal institutions and in a broader setting of informal learning. The authors conducted a sociological analysis of 20 biographical interviews with a heterogeneous set of individuals, including musicians, dancers and plastic artists. These interviews were a part of the research project on the social trajectories of migrant artists from the non-European Union countries living in Portugal. The results of the analysis show that formal and informal learning together with the migrant experience are intertwined and constitute the key factor in the configuration of migrant trajectories. There is often a mobility pattern across art styles, which makes differences between formal and informal circumstances in the life trajectories of migrant artists evident. Migration has a strong impact on the artistic work; this impact affects different areas of biographical experience: contact with the Portuguese culture, development of ethnic references, and participation in transnational art movements. The condition of immigrant artists generally implies a long trajectory of artistic training, including significant experiences of formal and informal learning in multiple social contexts throughout the life course. For those dedicated to the new transnational urban cultures (hip hop, graffiti, etc.), informal learning is the most important element. For those engaged in the traditional arts, the attendance of lengthy artistic programs seems to be a fundamental prerequisite for training and recognition. Together with the long and significant artists' investments in their education, the sociological study also revealed the great vulnerability (and precariousness) of their life trajectories, and the lack of structures supporting their access to the labor market.